The new wealth management : the financial advisor's guide to managing and investing client assets - Evensky, Harold; Horan, Stephen Michael; Robinson, Thomas R.; Evensky, Harold (Hoboken, N.J. : J. Wiley, 2011)
"Mainstay reference guide for wealth management, newly updated for today's investment landscape. For over a decade, The New Wealth Management: The Financial Advisor's Guide to Managing and Investing Client Assets has provided financial planners with detailed, step-by-step guidance on developing an optimal asset allocation policy for their clients. And, it did so without resorting to simplistic model portfolios, such as lifecycle models or black box solutions. Today, while The New Wealth Management still provides a thorough background on investment theories, and includes many ready to use client presentations and questionnaires, the guide is newly updated to meet twenty-first century investment challenges. The book includes expert updates from Chartered Financial Analyst (CFA) Institute, in addition to the core text of 1997's first edition - endorsed by investment luminaries Charles Schwab and John Bogle. Presents an approach that places achieving client objectives ahead of investment vehicles. Applicable for self-study or classroom use. Now, as in 1997, The New Wealth Management effectively blends investment theory and real world applications. And in today's new investment landscape, this update to the classic reference is more important than ever"--
Rev. ed. of: Wealth management. c1997.
Includes bibliographical references and index.
Includes bibliographical references and index.
Keywords: Portfolio management; Financial planners; Investment advisors; BUSINESS & ECONOMICS / Finance